TRANSFORMASI PEMASARAN DI ERA DIGITAL: PERAN VIRAL MARKETING DALAM MENDORONG MINAT BELI KONSUMEN E-COMMECERCE - Fadalirahman; Lailatul Maulida; Alyaa Destra A. F; Serli Febriyanti; Nurul Mustofa; Amir Furqon (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This research examines the transformation of marketing in the digital era by analyzing the role of Viral Marketing and Turbo Marketing on consumer Purchase Decisions, which is relevant to the context of e-commerce business development. Digital marketing, especially through social media, has become a crucial strategy for businesses, including startups such as cafes and culinary ventures, whose segmentation largely targets millennials. The method used is correlation research with a quantitative approach, using a sample of 100 visitors to Insomnia Café. The results of correlation and regression analysis, as well as the F-test and t-test, indicate that Viral Marketing and Turbo Marketing, both partially and simultaneously, have a significant influence on Purchase Decisions. Specifically, Viral Marketing is proven to have the most dominant influence on Purchase Decisions. These findings indicate that the strategy of spreading contagious messages and the support of service speed (Turbo Marketing) are highly effective in the digital environment. Although this study focuses on a café, the finding of the significant influence of Viral Marketing can be implied to e-commerce platforms as tangible evidence of the role of digital strategy in encouraging consumers to make purchase decisions. For future research, it is suggested to choose objects with more diverse populations and/or use other variables as intervening variables to enrich the findings.